More than one in two venous thromboembolism treated in French hospitals occurs during the hospital stays. (July 2016) - Allaert, Francois-André; Benzenine, Eric; Quantin, Catherine
Objective: The objective was to describe the prevalence of venous thromboembolism, pulmonary embolism, and deep vein thrombosis among hospitalized patients and the percentages of those occurring during the hospital stays. Methods: French DRG gave now the opportunity to investigate the frequency of venous thromboembolism occurring during the hospital stay. Statistics are issued from the national PMSI MCO databases encoded using the CIM10. Since 2010–2011 it is possible to differentiate the reason for hospital admission from the pathologies which secondly occurred. Any stay with the ICD-10 codes selected was considered as a hospital-occurred thrombosis unless it was the principal diagnosis of the first medical unit summary. To eliminate outpatient consultations or in day care, stays of <48 h were excluded. Results: The results pertain to the 78, 838, 983 hospitalizations in France from 2005 to 2011 and on the 18, 683, 603 hospital stays in 2010–2011. The incidence of hospital stays came to 860, 343 (1.09%) for venous thromboembolism, with 428, 261 (0.543%) for deep vein thrombosis without pulmonary embolism and 432, 082 (0.548%) for pulmonary embolism. It corresponds to an incidence of 189 per 100, 000 inhabitants. Out of 100 hospital stays involving venous thromboembolism, for 40.3% venous thromboembolism was the cause of hospitalization whereas 59.7% can be considered to have occurred during hospital stay. These distributions are of 25.6 and 74.4% for deep vein thrombosis, respectively, 53.8 and 46.2% for pulmonary embolism. Conclusion: The high proportion of hospital-occurred venous thromboembolism is an alarming situation that should question the quality of prevention and/or its effectiveness.